KEMAMPUAN MENGIDENTIFIKASI DAN MERUMUSKAN MASALAH BANGUN DATAR SERTA MINAT BELAJAR SISWA SMP - Indri Felani; Tsara Nabila Ramdhani; Heris Hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
One of the potential that can improve student competence about mathematic is problem solving ability, because the competence is mathematic’s heart. Student success for improving problem solving ability supported by students’s interest in learning activity. The reaserch approach conduct this research using qualitative with descriptive method. Sample in the research consist of 35 student at the VIII-E class in SMPN 3 Cimahi. Instruments used problem solving ability test and  interest in student learning scale non-tes. Based on research results obtained that problem solving ability is enough to achieve the criteria. Futhermore, the scala show that the half of student have good motivation in learning mathematics.